1999
DOI: 10.1136/thx.54.11.1009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of respiratory bronchiolitis on open lung biopsy and its relationship to smoking related interstitial lung disease

Abstract: Background-Respiratory bronchiolitisassociated interstitial lung disease (RBILD) is a rare form of interstitial lung disease which may present in similar fashion to other types of chronic interstitial pneumonia. The purpose of this study was to undertake a clinicopathological review of 10 patients with RBILD and to examine the clinical and imaging data related to its histopathological pattern, in particular the relationship of RBILD to smoking. Methods-Thirteen out of 168 retrospectively reviewed patients, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
214
2
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(240 citation statements)
references
References 17 publications
7
214
2
17
Order By: Relevance
“…The onset of RB-ILD is usually insidious with exertional dyspnea, symptomatic wheezing, and persistent cough, which may be non-productive, developing over a course of weeks or months [6][7][8]13]. This clinical picture can be masked by concomitant smoking-related chronic bronchitis.…”
Section: History and Physicalmentioning
confidence: 99%
See 4 more Smart Citations
“…The onset of RB-ILD is usually insidious with exertional dyspnea, symptomatic wheezing, and persistent cough, which may be non-productive, developing over a course of weeks or months [6][7][8]13]. This clinical picture can be masked by concomitant smoking-related chronic bronchitis.…”
Section: History and Physicalmentioning
confidence: 99%
“…In spite of the substantial clinical heterogeneity of these studies, it has been consistently reported that patients with RB-ILD are usually ever cigarette smokers with at least 30 pack-years at the time of diagnosis [6][7][8][9]12,13]. Only incidental single cases of RB-ILD in non-smokers have been reported, including patients exposed to second-hand smoke [8,16].…”
mentioning
confidence: 99%
See 3 more Smart Citations